Toward the Impact of English as a Foreign Language Teachers’ Grit and Self-Efficacy on Their Burnout - Zhou, Jinghan (Frontiers in Psychology, 2022)
Due to the adverse effects of teachers’ burnout on their professional performance, remarkable attention has been devoted to this mental state and its negative predictors. In this regard, multiple empirical research has been carried out to assess the effects of grit and self-efficacy as negative predictors of teacher burnout. Yet, no empirical or review study has delved into the impact of these variables at the same time. The current study attempts to fill this gap by delineating the impact of English as a Foreign Language (EFL) teachers’ grit and self-efficacy on their burnout. The significant role of grit and self-efficacy in curbing EFL teachers’ burnout was illustrated using theoretical and empirical evidence. The pedagogical implications are also offered.